Design para experiências na projetação de festas de aniversário infantis - Nichterwitz, Daniela Danni (Universidade do Vale do Rio dos Sinos, 2020)
Children's birthday parties are part of an economic sector that corresponds to 4.32% of Brazil's GDP. With billing of R$ 209 billion in 2013, it is estimated that the business for parties and events grows 14% per year. However, given the playful and relaxed nature of these rituals, little research has been carried out in this field. This work aimed to investigate the universe of birthday parties, as well as the experiences lived by users of these products and services, in order to explore the possibilities of action of Strategic Design in this area. In view of the complexity of this envisaged scenario, we decided to use the Metaprojectual approach, given the conditions that this methodology offers to gather, identify and analyze the information obtained, and, thus, compose a broad knowledge of the design problem. From the research carried out, it is suggested that birthday parties, as material and immaterial artifacts, are more than balloons with a decorated table in a place full of toys for children and snacks for parents: they carry a strong symbolic content. This content, which seems to be linked to the affirmation of our own identities. In this way, designing for experiences around the repertoire of events at a children's birthday party matches the need to offer subsidies to users have the autonomy to create their own value configurations, based on their personal capabilities
Keywords: Design estratégico; Design para experiências; Festas de aniversário infantis; Strategic Design; Design for experience; Cildren's birthday parties